Implementasi Pemberian Makanan Tambahan (PMT) sebagai Intervensi Gizi Terarah bagi Ibu dan Balita - Marlin, Diane; Astria, Niki; Rahmawati, Dwi; Badriyah, Lailatul; Nasution, Subang Aini; Sari, Yesi Mustika (Universitas Baiturrahim, 2025)
Nutritional problems in pregnant women, nursing mothers, and toddlers are still a major challenge in efforts to improve the degree of public health in Indonesia. One approach used to overcome this problem is through Provision of Additional Food (PMT) that is directed and based on local nutritional needs. This research or program aims to review the implementation of PMT as a form of nutritional intervention aimed at improving nutritional status and public awareness of the importance of balanced nutrition for mothers and children. This activity employed a pre-experimental design with a one-group pre-test and post-test approach. This design was chosen to determine the effect of Supplementary Feeding (PMT) and nutrition education on improving mothers’ knowledge and changes in the nutritional status of toddlers. The results showed a significant increase in mothers’ nutritional knowledge by an average of 32.75%, as well as an improvement in the nutritional status of toddlers, with the proportion of undernourished children decreasing from 60% to 20%. In addition, 85% of mothers reported being able to prepare nutritious supplementary foods using local ingredients after the program. The success of this activity was supported by the involvement of posyandu cadres, the selection of nutritious local food ingredients, and active community participation. In conclusion, PMT can be an effective nutritional intervention strategy in lowering the risk of malnutrition and improving the quality of maternal and child health, especially when coupled with extension and community-based approaches